Guerra Fiscal, Emenda Constitucional Nº 87/2015 e a possibilidade de aplicação do princípio In Dubio Pro Contribuinte - Guilherme Filho, Douglas (2020)
The Fiscal War in Brazil started since the moment when the ICM, a tribute with the characteristic of a federal tax, became the competence of the States, when it started to count on 27 different legislations, initiating a remedial levy by its product. In this sense, the States started to adopt measures aiming to increase the product of their collection, through the most varied forms of tax exemptions, although in an unconstitutional and unilateral way, in violation of the provisions of article 155, § 2, XII, paragraph “g” of the Federal Constitution. One of them, the so-called ICMS Protocol No. 21, although it did not meet the constitutional requirements for the creation of a new exemption, directly impacted the way the ICMS was collected and collected, giving rise to the issue of Constitutional Amendment No. 87/2015. The referred Constitutional Amendment changed the aspects of the matrix rule of tax incidence, notably the spatial aspect, but it was not enough to end the problem of the Fiscal War existing in our country, even after the Edition of Complementary Law No. 160/2017, which brought some ways of reducing conflicts on the topic. For no other reason, the adoption of the principle of in dubio pro contributor shows itself as an important instrument for resolving conflicts, notably due to the issue of EC No. 87/2015, in cases where there is doubt as to the factual aspects of the tax requirement tax, which is why his study will be developed throughout this work, as a way to end the serious problem of the Fiscal War existing in the country